Análise cinemática do nado crawl em jovens triatletas do programa Segundo Tempo - Rodrigues, Abraham Lincoln de Paula (2016)
Because it is a sport performed in liquid medium, where the density is higher than in the air, swimming is very dependent on technical skill. Thus, biomechanical factors influence on performance than the actual production capacity and release of energy for displacement. The aim of the study was to perform a kinematic analysis of the front crawl in young triathletes Second Half program. The participants were seven males aged between 13 and 16 years belonging to the program Triathlon Project Second Half of the Ministry of Sport practitioners of the sport for at least a month. Considering the relationship between the performance in swimming and the kinematic variables (FBr, DBr, VN and IB), significant correlations found in this study were with the FBR and is an important component of NV and one of the indicators of the propulsive efficiency. A significant correlation between FBr and the VN was observed in the search results. The results showed that the strategy used by athletes through sharp rise in FBR may be related to a low muscular endurance, preventing the maintenance or increase of DBr. According to the findings of the study it can be concludedthat the triathletes have used up increasing the FBr, with decreased DBr to increase the turnover.